Solitary Wave and Quasi-Periodic Wave Solutions to a (3+1)-Dimensional Generalized Calogero-Bogoyavlenskii-Schiff Equation (Advances in Applied Mathematics and Mechanics, 2018)
A (3+1)-dimensional generalized Calogero-Bogoyavlenskii-Schiff equationis considered, which can be used to describe many nonlinear phenomena in plasmaphysics. By virtue of binary Bell polynomials, a bilinear representation of the equationis succinctly presented. Based on its bilinear formalism, we construct soliton solutionsand Riemann theta function periodic wave solutions. The relationships betweenthe soliton solutions and the periodic wave solutions are strictly established and theasymptotic behaviors of the Riemann theta function periodic wave solutions are analyzedwith a detailed proof.